Acute radiation syndrome in large domestic animals with special reference to x- irradiation in goats - Wilkins, J. H. (The University of Edinburgh, 1965)
The author has interested himself in nuclear science especially as it affects veterinary medical matters for over fifteen years. He attended many Service courses on the subject and has written a number of theoretical articles. (Wilkins 1949, 1955, 1956, 1957, 1959). In 1960 he was posted to the Radiobiological Research Unit of the Medical Research Council at Harwell to help in a project to discover the effects of neutrons using large animals as the test subjects. His specific task was to acquire and maintain in health a large colony of goats. He took the opportunity to study some of the effects of X- irradiation on these animals and, in a very small measure, to put theory into practice. The study was divided into two sections : SECTION I was a general review of the acute radiation syndrome in domestic animals. SECTION II consisted of general observations on a colony of goats together with an investigation into certain aspects of the effects of X- irradiation on adult goats. The main significance of the work is in the fact that this is the first recording of data of the effects of whole body irradiation on a larger ruminant domestic animal in the United Kingdom. The general pattern of the findings is similar in most respects to that manifested by other animal species.
The acute radiation syndrome in large domestic animals with special reference to x- irradiation in goats